Antiepileptic Drug Withdrawal in Partial Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
The optimal time of discontinuing anticonvulsant treatment in children with cryptogenic partial epilepsy was evaluated at the Universities of Chieti and Siena, Italy.